Assessment on the halalness of gastrointestinal medication - Mohd Said, Nelly Isfandy (2015)
Muslims need their daily requirements such as food, medication, attire and others to be in halal state. This includes the gastrointestinal medications which are commonly used in hospitals where this study is done to assess that class of medication. The halal assessment was done by referring a few tools such as the drug information references and also the drug leaflets. From the total of 148 gastrointestinal pharmaceutical products that have been analyzed, 4.1 % are permissible, 29% are doubtful while none of them is categorized under impermissible. Majority of the products (66.9%) are unknown and could not be assessed as some information is unavailable. This is because some drug companies do not reveal the inactive ingredients of the products as for confidentiality issues. Pharmaceutical manufacturers, healthcare professionals, and religion scholars should fully cooperate with each other so that Muslims consumers get their halal medications.